Targeting the Swipe Generation in Islamic Communication: Adaptation of Digital Campaigns on the @millenial_hiro Account in the Political Constellation of Medan City Youth - Rakatiwi, Yolandha; Katimin, Katimin; Samosir, Hasrat Efendi (Journal Analytica Islamica, 2025)
This study aims to analyze the adaptation of digital campaigns carried out by the Instagram account @millenial_hiro in attracting the swipe generation in Medan City, through the approach of Islamic political communication and symbolic interactionism theory. The swipe generation, as a representation of productive-age youth, shows characteristics of critical, fast, and responsive information consumption to social media. The @millenial_hiro campaign strategy does not only use digital media to convey political programs, but also builds an interaction space based on the values of honesty, trustworthiness, justice, and benefit. This study uses a qualitative approach with descriptive methods, observation techniques, documentation, and content analysis based on the Klaus Krippendorff model. The findings show that various forms of content such as online game tournaments, educational microblogs, narrative talk, flow-talk, social experiments, and parody videos are used to create emotional resonance, strengthen political involvement, and form collective meanings rooted in Islamic values. Symbolic interactionism theory is used to read how digital symbols in the campaign build shared political meanings between candidates and youth. This study offers novelty by combining the perspectives of Islamic communication and symbolic interactionism in understanding the dynamics of digital political campaigns. The results of the study indicate that socio-political da'wah in the new media era can run effectively through a creative approach based on Islamic values, building a participatory, just, and civilized political culture among the younger generation. This study also opens up space for further studies on the transformation of Islamic political communication in the context of the development of digital technology.